2023
DOI: 10.1097/shk.0000000000002092
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Phenotypes of Sepsis-Associated Encephalopathy: A Retrospective Cohort Study

Abstract: Background: Sepsis-associated encephalopathy (SAE) is a dysfunction of the central nervous system experienced during sepsis with variable clinical and pathophysiologic features. We sought to identify distinct SAE phenotypes in relation to clinical outcomes. Methods: The Medical Information Mart for Intensive Care IV (MIMIC-IV) database and the eICU database were used to conduct a retrospective cohort study. Adult sepsis patients were included and SAE was defined as having a Glasgow Coma Scale (GCS) score ˂15 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Vital signs included systolic blood pressure (SBP), diastolic blood pressure (DBP), mean blood pressure (MBP), body temperature, heart rate, respiratory rate (RR), and pulse oximetry-derived oxygen saturation (SPO2). In addition, Glasgow Coma Scale (GCS) scores and Sequential Organ Failure Assessment (SOFA) scores were collected from each patient, and patients were categorized into a mild to moderate organ failure group and a severe organ failure group according to the SOFA 2 cut-off [ 11 13 ]. The endpoint of our study was in-hospital mortality, indicating the survival status at the time of discharge.…”
Section: Methodsmentioning
confidence: 99%
“…Vital signs included systolic blood pressure (SBP), diastolic blood pressure (DBP), mean blood pressure (MBP), body temperature, heart rate, respiratory rate (RR), and pulse oximetry-derived oxygen saturation (SPO2). In addition, Glasgow Coma Scale (GCS) scores and Sequential Organ Failure Assessment (SOFA) scores were collected from each patient, and patients were categorized into a mild to moderate organ failure group and a severe organ failure group according to the SOFA 2 cut-off [ 11 13 ]. The endpoint of our study was in-hospital mortality, indicating the survival status at the time of discharge.…”
Section: Methodsmentioning
confidence: 99%
“…In this investigation, SAE is defined as a Glasgow Coma Scale (GCS) score lower than 15 or a diagnosis of delirium ( 11 ). The Glasgow Coma Scale (GCS) was first described in 1974 and has since been widely used to assess a patient’s level of consciousness upon admission.…”
Section: Methodsmentioning
confidence: 99%
“…Sepsis-induced abnormalities in cerebral blood flow regulation contribute to SAE development. A recent study reported that individuals with sepsis who experience cerebrovascular autoregulation issues have reduced blood flow to the brain, leading to ischemic hypoxia and an increased risk of SAE development (103). In sepsis, infectious shock causes organ microcirculatory deficits and reduced cardiac output, which can lead to cerebral hypoperfusion, further contributing to cerebral ischemia and hypoxia.…”
Section: Abnormal Cerebral Blood Flow Regulationmentioning
confidence: 99%